Comparison of non-invasive radiographic measurements of soft tissue in the interdental space: a cadaver study. Issue 5 (June 2017) - Kniha, Kristian; Möhlhenrich, Stephan Christian; Peters, Florian; Yovev, Tsanko; Räsch, Manuel; Prescher, Andreas; Hölzle, Frank; Modabber, Ali
Abstract: When we use implants the aesthetic appearance of the patient is dependent to a large extent on identification of factors that influence the presence of interdental papillae. The aim of this study was to compare the accuracy of different non-invasive measurements to indicate the top of the interdental papilla on dental radiographs. The sample comprised six fresh, partly edentulous cadavers. The distance from the level of the interproximal bone next to the tip of the papilla was measured (n = 330) on standard radiographic images. Five different mixtures of radiopaque markers that had been used to highlight the top of the papilla in recently published studies were analysed. All measurements were compared with the bone probing length, which was evaluated clinically. The mixture of zinc oxide, eugenol cement, and tungsten powder (mean (SD) 0.14 (0.17) mm) deviated least from the control value. The deviation was significant (p < 0.01) between the zinc oxide, eugenol cement, and tungsten powder mixture and each of the other individual combinations. The most accurate non-invasive radiographic method of measuring the interproximal length of the papilla relative to the alveolar bone crest was therefore the mixture of zinc oxide, eugenol cement, and tungsten powder.